2001
DOI: 10.1046/j.1463-1318.2001.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of consultant‐led injection sclerotherapy compared with nurse practitioner‐led noninvasive interventions in the management of patients with first and second degree haemorrhoids

Abstract: A bulking agent and Nurse led education, advice and bowel habit retraining is as effective in reducing the incidence of bleeding from 1st and 2nd degree haemorrhoids as injection sclerotherapy. Patients who consult a NP with symptomatic 1st and 2nd degree haemorrhoids feel more empowered in the long term. Non-invasive bowel retraining methods should be offered as an alternative to more traditional, invasive treatments for patients with symptomatic early hemorrhoidal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…The initial treatment for hemorrhoids is conservative with fiber-rich diet and topical ointments. Treatment options that can be performed in an outpatient basis include procedures such as injection sclerotherapy, cryotherapy, photocoagulation, and rubber band ligation [14][15][16][17][18]. The Milligan-Morgan hemorrhoidectomy was considered until recently as the standard definite surgical treatment option for hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%
“…The initial treatment for hemorrhoids is conservative with fiber-rich diet and topical ointments. Treatment options that can be performed in an outpatient basis include procedures such as injection sclerotherapy, cryotherapy, photocoagulation, and rubber band ligation [14][15][16][17][18]. The Milligan-Morgan hemorrhoidectomy was considered until recently as the standard definite surgical treatment option for hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has shown that injections do benefit the patient, but that a single session using an adequate dose (5 ml of 5% phenol in each haemorrhoid) is as effective as multiple injections of a smaller dose [21]. Longer-term results show an improvement in 40% of patients at 4 years, but with 20% subsequently complaining of prolapse [22]. …”
Section: Outpatient Treatmentsmentioning
confidence: 99%
“…However, it is not helpful in treating a prolapse. Its main disadvantage is its low efficaciousness [4, 5]. Infrared coagulation is another outpatient procedure.…”
Section: Introductionmentioning
confidence: 99%